A STUDY ON BRAND AWARENESS TOWARDS HYUNDAI CARS IN TAMILNADU - Jaganathan, Dr.A.T.; Sakthivel, Mr. M.; Mohanraj, Mr.M. (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
The present article is an attempt that has been made to study the brand preference of customers with regard to Hyundai. The Hyundai marketers try to get the concentration of the customers in the manner of intention to get four wheeler cars in Hyundai models in Tamilnadu. The Hyundai marketers also try to initiate the Hyundai models and benefits of the consumers while purchase the car, mean while in India have stiff competition through foreign marketers dumping huge four wheeler, so the Hyundai marketers should know the taste and benefits of the consumers as on mind. This study makes an attempt to find out the brand that is successful in the market place able to convince the users about the used models of Hyundai car. The questionnaire was prepared through the inputs taken from the past researches and also from the feedbacks of the pilot study. Thus the validated final questionnaire was used to collect data from 105 respondents. The researchers have adopted convenient sampling technique to gather the data. The data are analyzed using the simple percentage analysis and weighted average methods. The result of this study reveals that levels of satisfaction and the overall performance of the Hyundai were good and satisfaction there is a no significant relationship between occupation and amount of money spent to purchase the Hyundai cars. Most of the respondents used to prefer the silky silver colour. Most of the respondents were used to influence by television ads in their Hyundai brand purchase. The study suggested that the advertisers need to focus on their effort to tab the market assuming the influence of the television ads in the Hyundai purchase behavior.